ANALISA PENGUJIAN MEKANIK TERHADAP VARIASI PENGGUNAAN BENTONITE DALAM PENGECORAN PINTU RUANG BAKAR: STUDI EKSPERIMEN DI PT. XYZ - Darmadi, Herry; Fatih Abdillah, Muhammad; Nurya Savitri, Agustin; Karti, Karti; Kurnia, Dian; Murhaban, Murhaban (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
The Combustion chamber door is a component of the boiler that functions to open and close the combustion chamber. At PT. XYZ, the combustion chamber door is made through the melting and metal casting method. In the metal casting method using a sand mold, an auxiliary substance in the form of bentonite is needed which functions to glue the sand mold and strengthen the mold so that it is not easily destroyed when receiving heat from the molten metal lava. The bentonite variations used in this study are 8%, 10%, and 12%. Mechanical testing (impact and hardness) is the most effective test to determine the description of the mechanical properties of a material. The purpose of this study is to determine the magnitude of the impact strength of the metal casting results in the manufacture of combustion chamber doors with different bentonite variations impact testing with the Charpy Impact Test method and the hardness value of the metal casting results in the manufacture of combustion chamber doors with different bentonite variations through hardness testing with the Rockwell Hardness Test method. In the impact test, the results of the impact strength analysis of the 8% bentonite variation were 0.1655 Kg.m/mm2, the 10% bentonite variation was 0.2119 Kg.m/mm2, and the 12% bentonite variation was 0.2555 Kg.m/mm2. In the hardness test, the results of the hardness analysis on the 8% bentonite variation were 104,7 HRC, the 10% bentonite variation was 92,1 HRC, and the 12% bentonite variation was 81,8 HRC.